2014
DOI: 10.1152/japplphysiol.00261.2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise contraction mode and protein supplementation on human skeletal muscle satellite cell content and muscle fiber growth

Abstract: Skeletal muscle satellite cells (SCs) are involved in remodeling and hypertrophy processes of skeletal muscle. However, little knowledge exists on extrinsic factors that influence the content of SCs in skeletal muscle. In a comparative human study, we investigated the muscle fiber type-specific association between emergence of satellite cells (SCs), muscle growth, and remodeling in response to 12 wk unilateral resistance training performed as eccentric (Ecc) or concentric (Conc) resistance training ± whey prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 67 publications
5
52
0
1
Order By: Relevance
“…More relevant, the myogenic program of elite junior cyclists was recently described and while fiber type-specific satellite cells were again not reported, the combined satellite cell count was ~13 SC/100 fibers (Frese et al, 2016), which is identical to the 13 SC/100 fibers observed here (11 SC/100 MyHC I fibers; 15 SC/100 MyHC II fibers). These numbers, especially the MyHC II population, are moderately higher than the 5–10 SC/100 muscle fibers typically found in untrained subjects (Snijders et al, 2015) and consistent with the 10–15 SC/100 muscle fibers reported in resistance-trained muscle (Petrella et al, 2008; Mackey et al, 2011; Suetta et al, 2013; Farup et al, 2014). The larger MyHC II SC pool in the present study is supported by previous training studies as both 14 weeks (Verney et al, 2008) and 10 weeks (Hoedt et al, 2016) of bicycle training led to more satellite cell accretion around MyHC II muscle fibers than MyHC I fibers.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…More relevant, the myogenic program of elite junior cyclists was recently described and while fiber type-specific satellite cells were again not reported, the combined satellite cell count was ~13 SC/100 fibers (Frese et al, 2016), which is identical to the 13 SC/100 fibers observed here (11 SC/100 MyHC I fibers; 15 SC/100 MyHC II fibers). These numbers, especially the MyHC II population, are moderately higher than the 5–10 SC/100 muscle fibers typically found in untrained subjects (Snijders et al, 2015) and consistent with the 10–15 SC/100 muscle fibers reported in resistance-trained muscle (Petrella et al, 2008; Mackey et al, 2011; Suetta et al, 2013; Farup et al, 2014). The larger MyHC II SC pool in the present study is supported by previous training studies as both 14 weeks (Verney et al, 2008) and 10 weeks (Hoedt et al, 2016) of bicycle training led to more satellite cell accretion around MyHC II muscle fibers than MyHC I fibers.…”
Section: Discussionsupporting
confidence: 76%
“…What is known of CHO+PRO intake around the time of aerobic exercise is that it can attenuate markers of proteolysis (Harber et al, 2010), reduce net protein breakdown (Koopman et al, 2004), increase protein synthesis and whole body protein balance (Howarth et al, 2009) and decrease markers of muscle damage compared to CHO or placebo treatments (Saunders et al, 2004; Valentine et al, 2008), altogether indicating that protein supplementation can be advantageous for skeletal muscle during periods of heavy exercise. Interestingly, there is compelling evidence that leucine provision can promote swift proliferative activity in pig myogenic progenitor cells (Han et al, 2008) and that whey protein supplementation in humans can expedite and amplify satellite cell dynamics following resistance exercise (Olsen et al, 2006; Farup et al, 2014). Therefore, when coupled with the idea that PRO supplementation was protective during ICT, it seems possible that the increase in MyHC I SC simply reflects enhanced myogenic sensitivity to exercise stress with PRO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second process results in myofiber enlargenment due to a decreased myonuclear domain resulting from activation and proliferation of myogenic satellite cells which fuse into muscle fibers, thereby providing additional myonuclei for augmented transcriptional activity and subsequent protein synthesis (Han et al 2008). Muscle damage that occurs in response to resistance exercise from both dynamic/isotonic (Willoughby & Nelson, 2002;Psilander et al 2003) and forced-lengthening (eccentric) muscle contractions (Farup et al 2014) have been shown to effectively increase markers of satellite cells activity and/or the number of activated satellite cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, delivery and uptake of carbohydrate (CHO) and protein may influence satellite cell activity, as it has recently been shown that both nutrients increased the number of satellite cells per myonuclei during recovery following eccentric exercise (Farup et al 2014). The mechanism(s) in which nutrient availability may increase myogenic activity is not well known but may be associated with the process in which CHO and branched-chain amino acids (BCAAs) contained in protein are able to increase muscle protein synthesis (Miller et al 2003) and upregulate intramuscular signaling cascades known to effect myogenic regulators such as ERK (Di Camillo et al 2014) and Akt (Ferreira et al 2014).…”
Section: Introductionmentioning
confidence: 99%